Legal Analysis of Ambiguity of Trademark Registration in Indonesia - Gunawan, Yusuf (Nurani, 2023)
The purpose of this research is to overcome dual identities or brands that have similarities in principle or in whole for similar and/or dissimilar goods or services that go side by side where the ownership rights are obtained through trademark registration or through a decision from the Supreme Court which is protected by law. as the identity of the goods and/or services being traded. The research method used is normative juridical. The formulation of the problems in this study are: 1. How is the regulation of trademarks that are rejected for registration that have similarities in principle or as a whole; 2. How to set a registered mark with a second identity. The findings of this research are based on Law Number 20 of 2016 concerning Trademarks and Geographical Indications (MIG) where trademarks are denied registration on the grounds of equality in principle and/or in whole for similar goods or not similar to other marks registered in bad faith belonging to other parties and the need for a second identity of a registered mark and/or a well-known mark in dealing with marks that are similar in principle and/or in whole that run side by side and required legal protection for registered marks to obtain legal certainty and there needs to be a scientific study of the proposed identities of the two brands.